## Solving the Equation (x + 1)(3x + 4) = 0

This equation is a quadratic equation in factored form. To solve it, we can utilize the **Zero Product Property**, which states that if the product of two or more factors is zero, then at least one of the factors must be zero.

**Step 1:** Set each factor equal to zero:

- x + 1 = 0
- 3x + 4 = 0

**Step 2:** Solve each equation for *x*:

- x = -1
- x = -4/3

**Therefore, the solutions to the equation (x + 1)(3x + 4) = 0 are x = -1 and x = -4/3.**

**Explanation:**

This equation represents a parabola that intersects the x-axis at two points. The x-coordinates of these points are the solutions we found. In other words, plugging in either x = -1 or x = -4/3 into the original equation will make the equation true.

**Important Note:**

The Zero Product Property is a powerful tool for solving quadratic equations in factored form. By setting each factor equal to zero, we can quickly and easily find the solutions.